Formulasi Ekstrak Buah Jambu Biji (Psidium guajava L.) sebagai Lotion Antioksidan - Ayu Sri Bulan; Lina Susanti; Rika Widyapranata (Fakultas Farmasi Universitas Setia Budi, 2014)
White guava (Psidium guajava, L.) fruit extract has antioxidant activity, because it contains quercetin, a flavonoid compound. Lotion is cosmetic preparations that widely used. This research was aimed to find out the antioxidant activity of lotion of white guava fruit extract. The white guava extract was made lotion preparation in three different concentrations of 18,5%; 20,5%, dan 22,5%. The three formulas were tested for its dispersive, adhesion, and viscosity. Determination of antioxidant activity in lotion was conducted by DPPH (1,1-diphenyl-2 pikrilhidrazil) using rutin as control and the results were calculated by IC50 value by probit analysis. The results showed that guava fruit extract lotion had antioxidant activity. Formula with the highest antioxidant activity was formula contained white guava fruit extract concentration of 22.5% with IC50 value of 131.83 ppm.